Uganda-Israel relations 1962-1972 "historical study" (Journal of the College of Basic Education, 2024)
The African continent occupied a special importance in the field of the foreign policy of the global Zionist movement in the period that preceded the establishment of Israel in 1948. However, this importance did not crystallize in its clear form until after Israel failed to acquire a position among the Afro-Asian countries, and its feeling of international isolation, as it helped A number of factors contributed to its rapprochement with the countries of the African continent and to gain its support in international forums. From here, Israel began extending “octopus” arms to various official and unofficial African institutions, sectors, and lobbies, until it was able, after a short period of time, to penetrate most of the countries of the continent and on a wide level of political, economic, military and cultural relations. According to these data, this research came to shed light on the nature of the Ugandan-Israeli relations between 1962-1972, as the first date represented the beginning of those relations after Uganda's independence from the British protectorate on 9/October/1962, while the second date represented the cessation of those relations in 31/march/1972. The research was divided into three main axes. The first axis dealt with the Ugandan-Israeli cooperation on the military and economic levels, as military and economic aid was the most prominent means of expanding Israeli influence in Uganda, while the second axis dealt with the Ugandan-Israeli political relations 1962-1972, while the third axis discussed The reasons for the Ugandan turn towards Israel in 1972.